Heart‐Specific Knockout of the Mitochondrial Thioredoxin Reductase (Txnrd2) Induces Metabolic and Contractile Dysfunction in the Aging Myocardium. Issue 7 (July 2015) - Kiermayer, Claudia; Northrup, Emily; Schrewe, Anja; Walch, Axel; de Angelis, Martin Hrabe; Schoensiegel, Frank; Zischka, Hans; Prehn, Cornelia; Adamski, Jerzy; Bekeredjian, Raffi; Ivandic, Boris; Kupatt, Christian; et al.
Abstract : Background: Ubiquitous deletion of thioredoxin reductase 2 ( Txnrd2 ) in mice is embryonically lethal and associated with abnormal heart development, while constitutive, heart‐specific Txnrd2 inactivation leads to dilated cardiomyopathy and perinatal death. The significance of Txnrd2 in aging cardiomyocytes, however, has not yet been examined. Methods and Results: The tamoxifen‐inducible heart‐specific α MHC‐MerCreMer transgene was used to inactivate lox P‐flanked Txnrd2 alleles in adult mice. Hearts and isolated mitochondria from aged knockout mice were morphologically and functionally analyzed. Echocardiography revealed a significant increase in left ventricular end‐systolic diameters in knockouts. Fractional shortening and ejection fraction were decreased compared with controls. Ultrastructural analysis of cardiomyocytes of aged mice showed mitochondrial degeneration and accumulation of autophagic bodies. A dysregulated autophagic activity was supported by higher levels of lysosome‐associated membrane protein 1 (LAMP1), microtubule‐associated protein 1A/1B‐light chain 3‐I (LC3‐I), and p62 in knockout hearts. Isolated Txnrd2 ‐deficient mitochondria used less oxygen and tended to produce more reactive oxygen species. Chronic hypoxia inducible factor 1, α subunit stabilization and altered transcriptional and metabolic signatures indicated that energy metabolism is deregulated. Conclusions: These results imply a novel role of Txnrd2 in sustaining heart function during aging and suggest that Txnrd2 may be a modifier of heart failure.